2007
DOI: 10.1177/1538192707305348
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Latinos/as for a Flat World

Abstract: Thomas Friedman's 2006 book, The World Is Flat: A Brief History of the Twenty-First Century, has caused both dialogue and controversy. This article explores implications of Friedman's ideas for the education of Latinos/as in American community colleges. A review of current literature addresses Hispanic demographics, workforce projections, the role of community colleges in workforce education, access and success issues, and strategies for serving Latinos/as effectively. Federal, state, and institutional policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Even though relatively few of these adult immigrants actually enter the U.S. educational system (particularly higher education) and their children often struggle to fit in it, they overwhelmingly view it as being open, accessible, and as a path to get ahead. They firmly believe in the benefits of education and in meritocracy and remain optimistic even in the face of seemingly insurmountable obstacles (see also González Sullivan 2007), perhaps to justify the sacrifices they have made in terms of opening opportunities for themselves and their children. However, given the Central Americans' legal marginality and their long-term temporary status, during which they have limited access to educational benefits and resources, their educational dreams become a moving target.…”
Section: Bifocal Lens That Shapes Their Dreamsmentioning
confidence: 99%
“…Even though relatively few of these adult immigrants actually enter the U.S. educational system (particularly higher education) and their children often struggle to fit in it, they overwhelmingly view it as being open, accessible, and as a path to get ahead. They firmly believe in the benefits of education and in meritocracy and remain optimistic even in the face of seemingly insurmountable obstacles (see also González Sullivan 2007), perhaps to justify the sacrifices they have made in terms of opening opportunities for themselves and their children. However, given the Central Americans' legal marginality and their long-term temporary status, during which they have limited access to educational benefits and resources, their educational dreams become a moving target.…”
Section: Bifocal Lens That Shapes Their Dreamsmentioning
confidence: 99%
“…Obama's challenge also comes at a time when obtaining a high school diploma or its equivalency is no longer enough of a credential to make a self-sustaining wage in the current labor market (Sullivan, 2007). In a 2002 study, labor market economists suggested that a strong employee is someone who has basic skills in reading, writing and math and is someone who has attained a job-training credential or postsecondary degree (Carnevale and Desrochers, 2002).…”
Section: Artistic Directormentioning
confidence: 99%
“…By opening up these alternative methods of degree attainment, individuals, like Liz, are able to receive integrate basic skills, while gaining the workforce competencies employers need to meet the growing middle skill demands and make a living wage (Sullivan, 2007;National Skills Coalition, 2014). This provides the learner with meaningful educational experiences where they can obtain necessary basic skills aligned to a workforce credential.…”
Section: Curtain Callmentioning
confidence: 99%
“…But, the composition of the high school graduates is different from 1992 to 2022 in all three of the regions. The Latino high school graduate population is increasing faster than the other segments and again, while this population is disproportionately represented in the community colleges (College Choice and Access to College, 2009;Kurlaender, 2006), this population does have a segment that (Sullivan, 2007). Thus, even community colleges serving Southwest, 1992Southwest, -2002 growing areas may find the need to effectively recruit traditional high school graduate students if they wish to increase this segment in their comprehensive community colleges;…”
Section: Identity Issues Among Community Collegesmentioning
confidence: 99%